Analysis of Factors Influencing Covid-19 Mortality Rate in Indonesia - Maunah, Ning; Susila, M. Endriyo; Kusumo, Mahendro Prasetyo (Jurnal Penelitian Pendidikan IPA, 2024)
Coronavirus disease 2019(Covid-19) which is caused by the SARS-CoV-2 virus, has a major impact on the high death rate. The positive confirmation rate is directly proportional to the Covid-19 death rate. The vaccination program is carried out to reduce the spread, reduce morbidity, mortality and achieve immunity from the SARS-CoV-2 virus. The aim of the research is to determine the effect of positive confirmation rates and vaccination rates on the Covid-19 death rate in Indonesia.The research is an observational study with a cross sectional approach.The population in this study were all patients with confirmed Covid-19. The samples were patients who were confirmed to have Covid-19 from February 2021 to March 2022. The analysis technique used was multiple linear regression. The research results show that the positive confirmation rate (p = 0.000) has a positive effect on the Covid-19 death rate, while the vaccination rate (p =0.278) and the second vaccination rate (p = 0.8619) had no effect on the Covid-19 death rate. It can be concluded that there is a positive and significant relationship between the number of positive confirmations and the Covid-19 death rate. The number of first and second vaccinations is not related to the Covid-19 death rate